Brooks And Chernyavskiy, Lenin And The Making Of The Soviet State - A Brief History With Documents - Fehr, Kregg (Teaching History: A Journal of Methods, 2009)
With this latest work, award-winning authors Jeffrey Brooks (Johns Hopkins University) and Georgiy Chernayavskiy (Kharkov University, Ukraine) have crafted a superb supplemental text for the classroom. Well-written, logically-ordered, brimming with documents, yet concise in its presentation, this slim volume is an engaging and easy read. Undoubtedly, many will find it an authoritative work as well, but leftists might be dissatisfied with the image of Lenin that it projects.